The Effect of Course Review Horay Type Cooperative Learning Model on Mathematics Problem Solving Ability of Class X Students of SMK NEGERI 3 GUNUNGSITOLI - Enike Zebua; Yulisman Zega (Edumaspul: Jurnal Pendidikan, 2023)
Mathematics is an important subject for students to master at school. However, in reality, students at SMK Negeri 3 Gunungsitoli still experience obstacles in solving mathematical problems because the learning process uses conventional learning models. So students are unable to answer the questions given by the teacher. The aim of this research is to find out whether there is an influence of the Course Review Horay learning model on students' mathematical problem solving abilities at SMK Negeri 3 Gunungsitoli. This type of research is quasi-experimental with a quantitative paradigm. The learning model used is the Course Review Horay model. The first step is to convey the material that will be presented, the second step is to explain the material, the third step is for students to discuss the material that has been explained. Furthermore, the results of this research were obtained based on hypothesis testing, namely tcount = 4.12 and ttable = 1.67 Because tcount = 4.12 > ttable = 1.67, then reject Ho and accept H1, which means: "There is an influence of the learning model Course Review Hooray on students' mathematical problem solving abilities. So it can be concluded that the Course Review Horay learning model has an influence on students' mathematical problem solving abilities.